Advanced polynomial problem

Algebra Level 3

Let P n ( x ) P_n (x) be a polynomial such that P n ( x ) = P n 1 ( x n ) P_n (x) = P_{n-1} (x-n) .

Given that P 0 ( x ) = x 90 x 89 + x 88 x 87 + + 1 P_0 (x)= x^{90} - x^{89} + x^{88} - x^{87} + \cdots + 1 , and P 10 ( x ) = P 0 ( x k ) P_{10} (x) = P_0 (x-k) , find k k .

54 44 55 45

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Anuj Soni
Apr 10, 2016

According to the question, P0(x) = x^90 - x^89 + x^88 -....... - x +1 now, P1(x) = P0(x-1) so, P1(x) = (x-1)^90 -(x-1)^89 ..... - (x-1) +1 and repeating these steps to P10(x) we get P10(x) = (x-55)^90 - (x-55)^89..... -(x-55) +1 therefore P10(x) = P0(x-55) hence k = 55

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...